Steps involved in activation of the complex of pro-matrix metalloproteinase 2 (progelatinase A) and tissue inhibitor of metalloproteinases (TIMP)-2 by 4-aminophenylmercuric acetate. - Itoh, Y; Binner, S; Nagase, H (1995)
Tissue inhibitor of metalloproteinases (TIMP)-2 forms a noncovalent complex with the precursor of matrix metalloproteinase 2 (proMMP-2, progelatinase A) through interaction of the C-terminal domain of each molecule. We have isolated the proMMP-2-TIMP-2 complex from the medium of human uterine cervical fibroblasts and investigated the processes involved in its activation by 4-aminophenylmercuric acetate (APMA). The treatment of the complex with APMA-activated proMMP-2 by disrupting the Cys73-Zn2+ interaction of the zymogen. This is triggered by perturbation of the proMMP-2 molecule, but not by the reaction of the SH group of Cys73 with APMA. The 'activated' proMMP-2 (proMMP-2*) formed a new complex with TIMP-2 by binding to the N-terminal inhibitory domain of the inhibitor without processing the propeptide. Thus the APMA-treated proMMP-2*-TIMP-2 complex exhibited no gelatinolytic activity. In the presence of a small amount of free MMP-2, however, proMMP-2* in the complex was converted into the 65 kDa MMP-2 by proteolytic attack of MMP-2, but the complex did not exhibit gelatinolytic activity. The gelatinolytic activity detected after APMA treatment was solely derived from the activation of free proMMP-2. The removal of the propeptide of the proMMP-2* bound to TIMP-2 was also observed by MMP-3 (stromelysin 1), but not by MMP-1 (interstitial collagenase). MMP-3 cleaved the Asn80-Tyr81 bond of proMMP-2*. On the other hand, when MMP-3 was incubated with the proMMP-2-TIMP-2 complex, it bound to TIMP-2 and rendered proMMP-2 readily activatable by APMA. These results indicate that the blockage of TIMP-2 of the complex with an active MMP is essential for the activation of proMMP-2 when it is complexed with TIMP-2.